2021
DOI: 10.1021/acs.jpcc.1c05461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Chloride on Internal Quasi-Liquid Layers in Ice Ih

Abstract: We consider the effect of sodium chloride on the properties of internal interfaces in ice I h . For this purpose, we employ molecular dynamics simulations to investigate the role of sodium and chloride ions in the properties of grain boundaries (GB), which are the interfacial regions separating adjacent crystal grains with different orientations. The results show that the presence of the ions significantly affects both the structural and dynamical characteristics of the disordered layers at the GB regions. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…7a). High salt concentrations in ice facilitate mechanical deformation, enhancing grain boundary sliding, as well as reducing the melting temperature of ice (De Almeida Ribeiro et al, 2021). If the muted reflectors identified (Fig.…”
Section: Scott-apfel Glaciermentioning
confidence: 99%
“…7a). High salt concentrations in ice facilitate mechanical deformation, enhancing grain boundary sliding, as well as reducing the melting temperature of ice (De Almeida Ribeiro et al, 2021). If the muted reflectors identified (Fig.…”
Section: Scott-apfel Glaciermentioning
confidence: 99%
“…Even for the bulk aqueous solution, the ion models with full integer charges (i.e., ±1e for alkali cations and halide anions) can also generate some unreasonable results, such as low solubility, sizable deviation of viscosity, and diffusion coefficients from experimental measurement. To improve the description of dynamical properties of ionic aqueous solution, Leontyev and Stuchebrukhov introduced a scaled charge ionic model to represent an electronic continuum correction, i.e., , where q represents the unscaled charge, is the scaling factor, and the ε el represents the dielectric constant. Many previous studies have shown that such simple scaling of ion charges can effectively improve the description of thermodynamic and dynamical properties of ionic aqueous solutions, e.g., the solubility, surface tension, enthalpies of solution, self-diffusion coefficients, and viscosity. Therefore, this seminal idea of scaled charge ionic model is quite helpful to understand thermodynamic behavior of ionic aqueous solutions. However, the full understanding of aqueous electrolytes in nanoscale confinement is still scarce due to the charge transfer, , as well as the anomalously low dielectric constant of confined solutions. …”
mentioning
confidence: 99%
“…This forcefield has been used to study the seawater/ice interface, the physical properties of seawater, and the effect of NaCl segregation in ice grain boundaries. 35,36…”
Section: Methodsmentioning
confidence: 99%
“…This forcefield has been used to study the seawater/ice interface, the physical properties of seawater, and the effect of NaCl segregation in ice grain boundaries. 35,36 MD simulations were carried out using the GROMACS 2020.3 program compiled in double-precision. 37,38 The MD equations of motion were integrated with a time step of 1 fs, which guarantees the conservation of total energy in a microcanonical test run with a total energy drift of approximately 5 Â 10 À5 eV per atom per ns.…”
Section: Methodsmentioning
confidence: 99%